ENGLISH TEACHING VIDEOS EMPLOYED IN EFL STUDENTS TEACHER CLASSROOM: A CASE STUDY OF STUDENTS’ PERCEPTION ON UTILIZING ENGLISH TEACHING VIDEO IN DEVELOPING TEACHING SKILLS - Hijjatul Qamariah (English Education Department, 2019)
This study tries to investigate the use of English teaching video in EFL student teacher classroom. It was initiated by the importance of providing authentic classroom teaching activities to the students. Employing English teaching videos to improve students teaching skills is alternatively important to do in order to gain a good insight of how native English teachers teach in the classroom. Therefore, some English teaching videos accessed from CELTA link, which is a platform of teaching practice for TESOL teachers were showed in the classroom. The implementation of the video was conducted for one semester, during teaching and learning process in the course of TEFL. The data are gained from the interview conducted with the students asking their opinion about English teaching videos whether they can affect students teaching ability. The result therefore reveals that the students agreed that English teaching videos help them learn more about teaching skills, classroom managements, student-teacher interaction and teaching methodology. However, they also stated that there was a weakness of the video that it is sometimes hard to understand. They stated that native speaker teachers’ talks could be difficult to understand sometimes.